AKUNTABILITAS PENGELOLAAN DANA DESA DI DESA SRIDADI KECAMATAN REMBANG KABUPATEN REMBANG TAHUN 2016 - Linda Widowati; R. Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
This research is based on the problem of the unpreparedness of village government in managing the Village Fund. This study aims to describe the accountability of Village Fund management using Elwood accountability theory and to analyze the factors that inhibit it. The research method used is descriptive qualitative with data collection method of interview, observation and document search. The selection of informants is done by purposive sampling technique. The results of the study and discussion show the discipline of procedural performance, role implementation, reporting and accountability to the regent and the community. Meanwhile, the results and objectives of the Village Fund empowerment have not done well. Sridadi Village Government experienced obstacles in understanding the rules and arranging the work structure. The limited resources of the apparatus, facilities and infrastructure, work culture and also society are the other factors that hinder the management of the Village Fund. This shows that the management of Village Funds in Sridadi Village has not been accountable. The researcher's recommendation to improve the accountability of Sridadi Village Fund management is that the government must disseminate the implementation of the village governance and management of the Village Fund, as well as to give education and training on the operation of the computer equipment to the village apparatus.